Castor oil‐based polyols with gradually increasing functionalities for biopolyurethane synthesis. Issue 4 (26th July 2019) - Park, Chang Kyu; Lee, Joo Hyung; Kim, Ick Soo; Kim, Seong Hun
ABSTRACT: In this research, castor oil‐based polyols with gradual increasing functionalities were prepared using thiol‐ene photo click reaction. The polyols were prepared by facile and efficient photo‐click reaction using thiols with different number of hydroxyl groups. The polyols were successfully synthesized using a modified bio‐oxygen demand (BOD) reactor and their structures were characterized. The hydroxyl number of the prepared polyols gradually increased depending on the thiol used for preparation. The increased hydroxyl number resulted in increased crosslinking densities for the prepared polyurethanes. The effect of the increasing crosslinking density and structure of the polyols on the mechanical and thermal properties of polyurethane were investigated. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48304. Abstract :